Design and construction of Xenoscope — a full-scale vertical demonstrator for the DARWIN observatory. (20th August 2021) - Baudis, L.; Biondi, Y.; Galloway, M.; Girard, F.; Manfredini, A.; McFadden, N.; Peres, R.; Sanchez-Lucas, P.; Thieme, K.
Abstract: The DARWIN observatory is a proposed next-generation experiment to search for particle dark matter and other rare interactions. It will operate a 50 t liquid xenon detector, with 40 t in the time projection chamber (TPC). To inform the final detector design and technical choices, a series of technological questions must first be addressed. Here we describe a full-scale demonstrator in the vertical dimension, Xenoscope, with the main goal of achieving electron drift over a 2.6 m distance, which is the scale of the DARWIN TPC. We have designed and constructed the facility infrastructure, including the cryostat, cryogenic and purification systems, the xenon storage and recuperation system, as well as the slow control system. We have also designed a xenon purity monitor and the TPC, with the fabrication of the former nearly complete. In a first commissioning run of the facility without an inner detector, we demonstrated the nominal operational reach of Xenoscope and benchmarked the components of the cryogenic and slow control systems, demonstrating reliable and continuous operation of all subsystems over 40 days. The infrastructure is thus ready for the integration of the purity monitor, followed by the TPC. Further applications of the facility include R&D on the high voltage feedthrough for DARWIN, measurements of electron cloud diffusion, as well as measurements of optical properties of liquid xenon. In the future, Xenoscope will be available as a test platform for the DARWIN collaboration to characterise new detector technologies.